Simultaneous determination of valsartan, amlodipine besylate and hydrochlorothiazide in tablets by near infrared - Natana Becker, Gabriela R. Foresti, Willian R. R. Almeida, Karine F. Nicorena, Marco F. Ferrão, Fabiana E. B. Silva (Journal of Applied Pharmaceutical Science, 2017)
Interval partial least-squares calibration (iPLS) and synergical partial least-squares calibration (siPLS) methods in combination with near infrared spectroscopy coupled with integrating sphere (NIRA) have been developed for simultaneous determination of amlodipine (AML), valsartan (VAL) and hydrochlorothiazide (HCT) in raw material powder mixtures used for production commercial pharmaceutical product (tablets). Variable selection methods (iPLS and siPLS) were applied to select a spectral range that provided significant information and models with lower prediction errors. A near-infrared reflectance accessory (NIRA) was used for direct sample analysis. Spectral data were acquired between 10000 - 4000 cm-1 and divided into 32 intervals. A relative standard error of prediction of 1.27% for VAL, 1.92% for HCT and 5.19% for AML was obtained after selection of better intervals by siPLS. Results shown that variable selection methods associated to NIRA is a relatively simple, free solvent and non-destructive procedure that could be applied to the simultaneous determination of AML, VAL and HCT in tablets.
Keywords: Chemometrics, Exforge HCT®, pharmaceutical, quality control.